PENETAPAN SIMA DALAM KONTEKS PERLUASAN WILAYAH PADA MASA MATARAM KUNA: KAJIAN BERDASARKAN PRASASTI-PRASASTI BALITUNG (899-910 M) - Tjahjono, Baskoro Daru; Rangkuti, Nurhadi (Berkala Arkeologi, 1998)
Among the kings who ruled the ancient Mataram Kingdom who published many inscriptions, one of them was Dyah Balitung. King Balitung ruled between the years 821 until 832 C or 899 to 910 AD and had a fairly large area of power. The inscriptions published by the king partly contain about the determination of sima, through these inscriptions will be studied how the context of the determination of a region to be sima with the process of expansion of territory in the ancient Mataram.